Advanced aerosol optical tweezers chamber design to facilitate phase-separation and equilibration timescale experiments on complex droplets. Issue 12 (1st December 2016) - Gorkowski, Kyle; Beydoun, Hassan; Aboff, Mark; Walker, Jim S.; Reid, Jonathan P.; Sullivan, Ryan C.
ABSTRACT: The phase-separation of mixed aerosol particles and the resulting morphology plays an important role in determining the interactions of liquid aerosols with their gas-phase environment. We present the application of a new aerosol optical tweezers chamber for delivering a uniformly mixed aerosol flow to the trapped droplet's position for performing experiments that determine the phase-separation and resulting properties of complex mixed droplets. This facilitates stable trapping when adding additional phases through aerosol coagulation, and reproducible measurements of the droplet's equilibration timescale. We demonstrate the trapping of pure organic carbon droplets, which allows us to study the morphology of droplets containing pure hydrocarbon phases to which a second phase is added by coagulation. A series of experiments using simple compounds are presented to establish our ability to use the cavity enhanced Raman spectra to distinguish between homogeneous single-phase, and phase-separated core–shell or partially engulfed morphologies. The core–shell morphology is distinguished by the pattern of the whispering gallery modes (WGMs) in the Raman spectra where the WGMs are influenced by refraction through both phases. A core–shell optimization algorithm was developed to provide a more accurate and detailed analysis of the WGMs than is possible using the homogeneous Mie scattering solution. The unique analytical capabilities of the aerosol optical tweezers provide a new approach for advancing our understanding of the chemical and physical evolution of complex atmospheric particulate matter, and the important environmental impacts of aerosols on atmospheric chemistry, air quality, human health, and climate change. Copyright © 2016 American Association for Aerosol Research